2004
DOI: 10.1007/s00018-004-4276-8
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic protein tyrosine kinases

Abstract: RET is the receptor for glial-derived neurotrophic factor growth factors. It is a paradigm of a single gene that causes different types of human cancer when targeted by different genetic alterations. Like other receptor tyrosine kinases, once activated, RET recruits a variety of signaling molecules that mediate biological responses. Here we review data on the signaling pathways that lead to RET-mediated cell transformation and recent evidence that manipulation of RET holds promise for thyroid cancer treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(19 citation statements)
references
References 69 publications
0
19
0
Order By: Relevance
“…It is well known that oncogenic RET proteins cause cell transformation by modifying intracellular signal Oncogenic potential of RET mutations N Miše et al transduction (Santoro et al, 2004;Marx, 2005). Activation of the phosphatidylinositol 3-kinase (PI3K)/Akt pathway, for example, which regulates cellular survival (Besset et al, 2000), has been shown to be required for RET-mediated transformation (Segouffin-Cariou and Billaud, 2000;Drosten et al, 2004).…”
Section: Signaling Pathways Constitutively Activated By Different Retmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that oncogenic RET proteins cause cell transformation by modifying intracellular signal Oncogenic potential of RET mutations N Miše et al transduction (Santoro et al, 2004;Marx, 2005). Activation of the phosphatidylinositol 3-kinase (PI3K)/Akt pathway, for example, which regulates cellular survival (Besset et al, 2000), has been shown to be required for RET-mediated transformation (Segouffin-Cariou and Billaud, 2000;Drosten et al, 2004).…”
Section: Signaling Pathways Constitutively Activated By Different Retmentioning
confidence: 99%
“…However, this phenotype is less frequent but clinically more aggressive (Santoro et al, 2004). Over 90% of all MEN 2B mutations occur in codon 918.…”
Section: Introductionmentioning
confidence: 99%
“…These ligands bind RET through GPIanchored coreceptors (Santoro et al, 2004). RET genetic alterations are responsible for the occurrence of two thyroid malignancies, the medullary (MTC) and the papillary thyroid carcinomas (PTC).…”
Section: Introductionmentioning
confidence: 99%
“…Germline point mutations in RET cause MTC in the context of three related dominantly inherited tumor syndromes, multiple endocrine neoplasia type 2A (MEN2A), multiple endocrine neoplasia type 2B (MEN2B) and familial medullary thyroid carcinoma (FMTC). RET point mutations are also found in a fraction of sporadic MTCs (Santoro et al, 2004). PTC is the most common endocrine malignancy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation